Front Porch, Small House: A Longitudinal Study of Team and University Identification Among Incoming Students at a Division III University - Katz, Matthew; Dixon, Marlene A.; Heere, Bob; Bass, Jordan R. (Journal of Intercollegiate Sport, 2017)
In this longitudinal study, the authors examined the relationship between team identification and university identification for 37 incoming college first year students at a National Collegiate Athletic Association (NCAA) Division III institution. After collecting four waves of data from the same participants over the course of two years, the authors utilized growth curve analysis to examine the development and trajectories of the students’ levels of identification with both the university and the intercollegiate sport teams. Furthermore, the authors empirically measured if identifying with the athletic teams on campus explained any variance in one’s identification with the larger university. Finally, this study was explicitly conducted within the context of a Division III institution to increase understanding of the social value of Division III athletics for students not directly participating as student-athletes. The presented findings provide a longitudinal account of the psychological and social value of Division III sport teams in terms of building a stronger connection between new students and the larger university.